Feeding Your Preschooler: Helping in the Kitchen - Ashley R. Kendall; Karla P. Shelnutt; Gail P. A. Kauwell (EDIS)
Encouraging your child to help in the kitchen is a great way to get them more interested in the food they eat and in trying new foods. Helping out in the kitchen also allows your preschooler to learn lifelong skills. This 2-page fact sheet suggests ways to get your preschooler helping in the kitchen as well as the benefits of working side-by-side to prepare family meals and snacks. Written by Ashley R. Kendall, Karla P. Shelnutt, and Gail P. A. Kauwell, and published by the UF Department of Family, Youth and Community Sciences, March 2012.